Evidence for Individual Face Discrimination in Non-Face Selective Areas of the Visual Cortex in Acquired Prosopagnosia - Laurence Dricot; Bettina Sorger; Christine Schiltz; Rainer Goebel; Bruno Rossion (Behavioural Neurology)
Two areas in the human occipito-temporal cortex respond preferentially to faces: ‘the fusiform face area’ (‘FFA’) and the ‘occipital face area’ (‘OFA’). However, it is unclear whether these areas have an exclusive role in processing faces, or if sub-maximal responses in other visual areas such as the lateral occipital complex (LOC) are also involved. To clarify this issue, we tested a brain-damaged patient (PS) presenting a face-selective impairment with functional magnetic resonance imaging (fMRI). The right hemisphere lesion of the prosoagnosic patient encompasses the ‘OFA’ but preserves the ‘FFA’ and LOC [14,16]. Using fMRI-adaptation, we found a larger response to different faces than repeated faces in the ventral part of the LOC both for normals and the patient, next to her right hemisphere lesion. This observation indicates that following prosopagnosia, areas that do not respond preferentially to faces such as the ventral part of the LOC (vLOC) may still be recruited to subtend residual perception of individual faces.